Pengaruh Kesesuaian Harga, Promosi Dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Hotel Aston Inn Mataram - Rofika Dwi Yatnas; Zulkarnaen; Ulfiyani Asdiansyuri (Kredibel: Jurnal Ilmiah Manajemen, 2025)
This research aims to examine the influence of price suitability, promotion and service quality on customer loyalty at the Aston Inn Mataram Hotel. This type of research is associative. Research population of Aston Inn Mataram Hotel customers. The sample was 60 respondents. Questionnaire data collection techniques. Data analysis using multiple linear analysis shows (Y = 0.145 – 0.099X1 + 0.032X2 + 1.026X3 + e). Based on the results of partial hypothesis testing, price suitability has no significant effect on customer loyalty at the Aston Inn Mataram Hotel with a t value of -0.678 < 2.003, promotions have no significant effect on customer loyalty at the Aston Inn Mataram Hotel with a t value of 0.271 < 2.003, and service quality has an effect significant to Aston Inn Mataram Hotel customer loyalty with a calculated t value of 6.233 > 2.003. Simultaneously, suitability of price, promotion and service quality have a significant effect on customer loyalty at the Aston Inn Mataram Hotel with F count 50.376 > 2.76 with a significant value of 0.000 < 0.05. Service quality is the most dominant variable that influences customer loyalty at the Aston Inn Mataram Hotel with a beta value of 0.897.